Transformative urban mobility: comparative analysis of global transit-oriented development strategies / Nurulhuda Ali ... [et al.] - Ali, Nurulhuda; Alias, Anuar; Hamzah, Hasniyati; Muhammad, Ismail; Othman, Khairul Nizam (School of Civil Engineering, 2025)
The urban mobility landscape is undergoing unprecedented transformation, driven by complex global transportation, sustainability, and urban development challenges. This comparative study critically examines Transit-Oriented Development (TOD) strategies across six cities, representing geographical developmental contexts, employing a rigorous analytical framework to deconstruct urban mobility transformation approaches. The research reveals nuanced strategies for mobility integration through systematic comparative analysis, identifying key mechanisms that enable successful urban transportation redesign. The study uncovers distinctive patterns of institutional innovation, policy adaptation, and technological integration that characterise transformative urban mobility strategies. Critical insights emerge highlighting how cities with different socioeconomic backgrounds develop unique yet interconnected approaches to urban transportation challenges. The research provides a comprehensive comparative lens, demonstrating that effective urban mobility transformation transcends geographical boundaries, requiring adaptive, context-sensitive strategic frameworks that balance technological innovation, social equity, and sustainable development objectives.